How do I get them to write? explore the reading-writing connection using freewriting and mentor texts to motivate and empower students - Filewych, Karen (Pembroke Publishers, 2017)
"This remarkable book shows teachers how to inspire students to learn to write and write to learn. Committed to the premise that all students can learn to write with appropriate teaching, modelling, and practice, it argues that reading and writing go hand in hand. Through reading, writing, and the inevitable discussions that follow, students learn from the experiences of others, open their minds to many possibilities, gain a glimpse into worlds unknown to them, make connections to their own lives, and reflect on their own choices and learning. This practical book shows you how to use freewriting and powerful mentor texts to create classrooms where students enjoy putting pencil to paper and taking the necessary risks to grow and flourish as writers. An ideal resource for teachers who love writing as well as those who find it challenging."--